Uso das profilaxias pós-exposição e pré-exposição no Brasil na prevenção combinada do HIV (2011-2019). - Kennedy Crepalde Ribeiro (2022)
Introduction: The combination HIV prevention framework includes multiple interventions that can be used to prevent HIV infeccion. HIV post-exposure prophylaxis (PEP) and HIV pre-exposure prophylaxis (PrEP) are available through the Unified Health System. The effectiveness of these prophylaxes against HIV infection has been found in the literature, however there is little national evidence on the use of PEP and PrEP. Objectives: The overall objective of this work was to evaluate the use of PEP following consensual sexual exposure (PEPSE) and PrEP in Brazil. The specific objectives were to: assess the trend in the PEPSE prevalence and the proportion of people who repeated PEPSE within 365 days between 2011 and 2019 (Study 1); evaluate the most dispensed antiretroviral regimens for PEPSE between 2011 and 2019 (Study 1); identify people characteristics among who used or repeated PEPSE in 2018 (Study 1); analyse PrEP adherence during 365 days among people initiating prophylaxis in 2018 (Study 2); and identify characteristics of people and services independently associated with PrEP adherence during 365 days (Study 2). Methods: Both studies have, as a data source, the dispensations registries in the Medicines Logistic Control System (Siclom). In study 1, it was analyzed the trends in the prevalence of PEPSE per million (2011-2019) and the trends in proportion of people who repeated PEPSE in 365 days since the first PEPSE dispensation (2011-2018), in Brazil, using joinpoint regression. Furthermore, the prevalence of repeated PEPSE was compared according to the characteristics of the people and services in 2018, the most recent year available. In study 2, adherence to PrEP was estimated using the proportion of days covered (PDC) from the first date of dispensing to 365 days of follow-up, for people with an index year of 2018. Adherence to treatment was considered PDC ≥ 60 %. To determine the characteristics associated with adherence, a mutually adjusted logistic regression analysis was performed. Sensitivity analyzes were performed raising the adherence threshold (PDC ≥ 80%); or considering lost of follow-up. Results: In Study 1, with 198,801 people included, it was observed that the prevalence of PEPSE increased 55.5% between 2011-2019. The most frequent antiretrovirals prescribed for PEPSE in the period followed the national clinical recommendations in force at each time. The proportion of people who repeated PEPSE increased by 11.8% since 2011, reaching the proportion of 8.4% among people with first dispensing in 2018. Characteristics associated with a higher prevalence of repeated PEPSE use: cisgender men, transgender women, homosexuals, young adults (25-29 years old), medicines dispensing units in cities with more than 500,000 inhabitants, or health services with a greater number of people. It is important to offer combination HIV prevention to people, especially populations with a higher prevalence of PEPSE repetition. In Study 2, including 5,131 people initiating PrEP in 2018, 68% had PrEP adherence (proportion of days covered ≥60%) whitin 365 days. It was also observed that 11.5% of people had a single dispensing of PrEP in one year. The following factor were associated with adherence: cisgender men, under 40 years old, homosexuals/gays/lesbians, having 12 or more years of schooling and living in the Southeast region. Using PDC ≥ 80%, the proportion of adherent people decreased to 56.0%; considering lost of follow-up, the proportion of adherent persons increased to 91.6%. However, the characteristics associated with adherence remained similar. Conclusion: The findings of these studies indicate the importance of offering combination HIV prevention, especially in the case of populations with a higher prevalence of PEPSE repetition, as well as the need to reinforce and develop public health policies aimed at improving adherence to PrEP for maximum effectiveness.